Chemical constituents of essential oils from aerial parts of Adenosma capitatum and Limnophila aromatica - Bhuiyan, Mohammad Nazrul Islam; Akter, Farhana; Chowdhury, Jasim Uddin; Begum, Jaripa (Bangladesh Journal of Pharmacology, 2010)
<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">The essential oils were isolated by hydrodistillation from the aerial parts of <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Adenosma capitatum<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> and <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Limnophila aromatica<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> and were analyzed by gas chromatography mass spectrometry (GC-MS). Forty six and thirty components were identified, representing 98.8% and 99.3% of the total oils respectively. Oil of <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">A. capitatum<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> rich in <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">limonene (24.74%), fenchone<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> (21.59%) and 2-carene (17.64%). On the other hand, <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; font-style: italic; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">L. aromatica <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">rich in <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">Z-ocimene<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US"> (39.21%), <span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">terpinolene (17.24%) and<span style="font-size: 9.0pt; font-family: 'Book Antiqua'; mso-default-font-family: 'Book Antiqua'; mso-ascii-font-family: 'Book Antiqua'; mso-latin-font-family: 'Book Antiqua'; mso-greek-font-family: 'Book Antiqua'; mso-cyrillic-font-family: 'Book Antiqua'; mso-armenian-font-family: Sylfaen; mso-hebrew-font-family: 'Times New Roman'; mso-arabic-font-family: 'Times New Roman'; mso-devanagari-font-family: Mangal; mso-bengali-font-family: Vrinda; mso-gurmukhi-font-family: Raavi; mso-oriya-font-family: Kalinga; mso-tamil-font-family: Latha; mso-telugu-font-family: Gautami; mso-kannada-font-family: Tunga; mso-thai-font-family: 'Angsana New'; mso-georgian-font-family: Sylfaen; mso-latinext-font-family: 'Book Antiqua'; mso-bidi-font-weight: bold; language: en-US; mso-ansi-language: en-US; mso-bidi-language: ar-SA;" lang="en-US">camphor (12.89%).